An assessment of solar power contribution to electric vehicle - Luo, Chuan. (2013)
This is a project to assess the extent by which solar energy technology could contribute to Electric Vehicles’ (EVs) charging in real world’s investment, based on the idea of battery swapping stations raised by Batter Place Company and the assumption that all the existing conventional vehicles in Singapore is to be replaced by the environmentally friendly EVs. In order to achieve this goal, current Singapore’s energy consumption and available solar irradiation is used and an optimized real-time charging scheme is designed based on 24hours-ahead solar irradiation forecast and tariff prediction. Artificial Neural Network (ANN) is employed in the project to forecast the solar irradiation of the coming 24 hours. The optimized real-time charging scheme will make use of the predicted solar irradiation, expected future EV energy demand and demand-based tariff to design a cheapest real-time charging plan at battery swapping stations. Base on all the steps mentioned above, a comprehensive comparison between the cost of investment on employing Photovoltaic System in swapping stations and the revenue earned by the system will be studied.